Impact of agro-geotextiles on soil aggregation and organic carbon sequestration under a conservation-tilled maize-based cropping system in the Indian Himalayas - Roy, Plabani; Bhattacharyya, Ranjan; Singh, Raman Jeet; Sharma, N. K.; Kumar, Gopal; Madhu, M.; Biswas, D. R.; Ghosh, Avijit; Das, Shrila; Joseph, Ann Maria; Das, T. K.; Kumar, Soora Naresh; et al. (Frontiers in Environmental Science, 2023)
Although agro-geotextile (AGT) emplacement shows potential to mitigate soil loss and, thus, increase carbon sequestration, comprehensive information is scanty on the impact of using agro-geotextiles on soil organic carbon (SOC) sequestration, aggregate-associated C, and soil loss in the foothills of the Indian Himalayan Region. We evaluated the impacts of Arundo donax AGT in different configurations on SOC sequestration, aggregate stability, and carbon management index (CMI) since 2017 under maize-based cropping systems on a 4% land slope, where eight treatment procedures were adopted. The results revealed that A. donax placement at 0.5-m vertical-interval pea–wheat (M + AD10G0.5-P-W) treatment had ∼23% increase in SOC stock (27.87 Mg·ha−1) compared to the maize–wheat (M-W) system in the 0–30-cm soil layer. M + AD10G0.5-P-W and maize–pea–wheat treatments under bench terracing (M-P-W)BT had similar impacts on SOC stocks in that layer after 5 years of cropping. The total SOC values in bulk soils, macroaggregates, and microaggregates were ∼24, 20, and 31% higher, respectively, in plots under M + AD10G0.5-P-W treatment than M-W in the topsoil (0–5 cm). The inclusion of post-rainy season vegetable pea in the maize–wheat cropping system, along with AGT application and crop residue management, generated additional biomass and enhanced CMI by ∼60% in the plots under M + AD10G0.5-P-W treatment over M-W, although M + AD10G0.5-P-W and (M-P-W)BT had similar effects in the topsoil. In the 5–15-cm layer, there was no significant effect of soil conservation practices on CMI values. Under the M + AD10G0.5-P-W treatment, the annual mean soil loss decreased by ∼92% over M-W treatment. We observed that CMI, proportion of macroaggregates, aggregate-associated C, labile C, total SOC concentration (thus, SOC accumulation rate), and mean annual C input were strongly correlated with the mean annual soil loss from 2017 to 2021. The study revealed that the emplacement of an A. donax mat and incorporation of a legume in a cropping system (M-W), conservation tillage, and crop residue retention not only prevented soil loss but also enhanced C sequestration compared to farmers’ practice (M-W) in the Indian Himalayas. The significance of this study is soil conservation, recycling of residues and weeds, and climate change adaptation and mitigation, as well as increasing farmers’ income.